The Importance of Learning Vocabulary by Features in Building the Lexical Ability of the Learner of Arabic Language as a Second Language: Language Acquisition - Elmaskin, Yassin (Al-Ḍād Journal, 2022)
Through the current article, we seek to address one of the important problems facing the process of teaching and learning Arabic as a second language, mainly related to the vocabulary component. In order to defend the proposed proposition, which is to highlight the role of features in building the lexical ability of the learner of Arabic as a second language, we divided the article into three main axes. In the first axis, they discussed the role of traits in building entrances (listening and reading), in the second axis their role in storing vocabulary, and in the third axis their role in the production process (writing and speaking). Through all of this, we concluded that traits play an important role in building the lexical destiny of the learner of Arabic as a second language. Keywords: words, traits, word power, Arabic as a second language